Fracture of Proximal Humerus & Shaft Managed With Closed Reduction & External Fixation by Joshi External Stabilisation System (Jess) – A Case Report - Kandel, Prakriti Raj; Baral, Rajiv; Thakur, Abhishek Kumar; Singh, Gyaneshwar Prasad; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2018)
We are presenting a case of proximal humerus& shaft fracture in a 50 year old female. She sustained injury on her left upper limb in a road traffic accident. It was managed with closed reduction & external fixation by Joshi External Stabilisation System (JESS). Lacerated wound over her left shoulder & arm region was managed with skin grafting. The post-operative period was uneventful. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, Page: 54-58